Reconstructing a Network of Circulation and Dominican Patronage: The Case of the Tolosan Master of the Avignon Decretum (Avignon, BM, Ms. 659) - Maria Alessandra Bilotta (Intrecci d'arte)
The manuscripts presented in this contribution, Ms. lat. 362 and Ms. lat. 16905, preserved in the Bibliothèque nationale de France, have so far been overlooked by art historians. The stylistic analysis of the illustrative and decorative apparatus of these manuscripts, conducted in this study, makes it possible to attribute them to the anonymous illuminator called Master of the Avignon Decretum (from the most relevant manuscript illuminated by him, Avignon, Bibliothèque Municipale, Ms. 659). This illuminator, trained most probably in Toulouse and active between 1320 and 1350, most likely worked for the Dominicans of the city.